2003
DOI: 10.1152/ajpcell.00359.2002
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of chloride permeability by endogenously produced tyramine in the Drosophila Malpighian tubule

Abstract: The Malpighian (renal) tubule of Drosophila melanogaster is a useful model for studying epithelial transport. The purpose of this study was to identify factors responsible for modulating transepithelial chloride conductance in isolated tubules. I have found that tyrosine and several of its metabolites cause an increase in chloride conductance. The most potent of these agonists is tyramine, which is active at low nanomolar concentrations; the pharmacology of this response matches that of the previously publishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
82
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(83 citation statements)
references
References 55 publications
1
82
0
Order By: Relevance
“…Similarly, rearing the larvae on the K-rich diet and bathing them in haemolymph from the same group stimulates fluid and K + secretion, and thapsigargin does not produce further stimulation. Taken together, the results suggest that the diuretic factors responsible for the increase in fluid secretion and K + secretion in tubules isolated from larvae reared on salt-rich diets may act through increases in intracellular Ca (Blumenthal, 2003) are mediated through an increase in intracellular Ca 2+ in the stellate cells. The increase in intracellular Ca 2+ in turn leads to an increase in transepithelial chloride permeability and a consequent collapse of the transepithelial potential.…”
mentioning
confidence: 69%
“…Similarly, rearing the larvae on the K-rich diet and bathing them in haemolymph from the same group stimulates fluid and K + secretion, and thapsigargin does not produce further stimulation. Taken together, the results suggest that the diuretic factors responsible for the increase in fluid secretion and K + secretion in tubules isolated from larvae reared on salt-rich diets may act through increases in intracellular Ca (Blumenthal, 2003) are mediated through an increase in intracellular Ca 2+ in the stellate cells. The increase in intracellular Ca 2+ in turn leads to an increase in transepithelial chloride permeability and a consequent collapse of the transepithelial potential.…”
mentioning
confidence: 69%
“…cAMP and cGMP have been shown to play a role in stellate cells (Kerr et al, 2004), although the endogenous pathways for cAMP and cGMP are not known for this tubule cell type. Recent research, however, has demonstrated that cGMP acting through DG1 (but not DG2) can inhibit transepithelial responses induced by both tyramine and D. melanogaster leucokinin (Ruka et al, 2013), both of which increase calcium signalling and chloride conductance (Blumenthal, 2003;Cabrero et al, 2013;O'Donnell et al, 1996;Radford et al, 2004;Terhzaz et al, 1999). Thus, a yet-unidentified inhibitory process for tyramine and D. melanogaster leucokinin signalling in stellate cells is cGMP/DG1-mediated.…”
Section: Camp Signallingmentioning
confidence: 99%
“…Furthermore, OA and TA receptor distributions in the insect CNS differ considerably from each other [J. Erber (Technical University Berlin, Berlin, Germany), personal communication]. Functionally, exogenous TA increases chloride conductances in Drosophila malphigian tubules (Blumenthal, 2003), alters body wall muscle excitatory junction potentials (Kutsukake et al, 2000), and can rescue cocaine sensitization in Drosophila (McClung and Hirsh, 1999). In mammals, the physiological roles for trace amines such as TA and OA are mostly unknown, but they have been implicated in a variety of neurological disorders (Branchek and Blackburn, 2003), and receptors specific for TA have been identified (Borowsky et al, 2001).…”
Section: Ta As Neurotransmitter/modulatormentioning
confidence: 99%